2012
DOI: 10.1136/annrheumdis-2011-201164
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI measures of cartilage predict knee replacement: a case–control study from the Osteoarthritis Initiative

Abstract: Abstract:Objective: Knee osteoarthritis is a highly prevalent disease, commonly requiring joint replacement; it substantially reduces quality of life and increases health care utilization and costs. We aimed to identify whether quantitative measures of articular cartilage structure predict knee replacement, and to establish their utility as outcomes in clinical trials of disease modifying therapy. Methods:A nested case-control study was performed in Osteoarthritis Initiative participants, a multicenter observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 57 publications
6
110
4
Order By: Relevance
“…Quantitative MRI measures of cartilage thickness loss were shown to contribute to prediction of knee replacement in a 4-year natural history study of OA (26). However, we lack an estimate of the extent of structural modification required to provide patient benefit in the clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative MRI measures of cartilage thickness loss were shown to contribute to prediction of knee replacement in a 4-year natural history study of OA (26). However, we lack an estimate of the extent of structural modification required to provide patient benefit in the clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…The primary end point (central subregions of the medial femorotibial compartment) was selected because previous results indicated that the central medial femorotibial compartment shows the greatest rate of change and sensitivity to change in cartilage thickness (20,24,26,42). In light of the previous trials showing more marked treatment effects on the lateral knee compartment as compared to the medial knee compartment (40,41), it is interesting to note that the primary end point of the present trial was not met, while dose-dependent treatment effects were found for the lateral knee compartment (lateral femorotibial compartment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, arthroscopy demonstrates only the articular surface and does not allow evaluation of other important tissues, such as the subchondral bone, and it is not feasible to invasively assess knee joints in an observational study over several time points. By using a similar casecontrol design but a quantitative MR imaging approach that allows assessment of different cartilage metrics, we have recently shown that cartilage thickness in the central medial tibiofemoral compartment is diminished in knees undergoing knee replacement compared with those that do not (15).…”
Section: Discussionmentioning
confidence: 99%
“…Since joint preservation represents the ultimate clinical goal of any therapeutic attempt, imaging biomarkers that allow prediction of joint replacement may serve as prognostic markers, may aid in the decisionmaking process for surgery, and may eventually replace radiographic joint space assessment in disease modification trials as an intervention effectiveness marker (14,15).…”
Section: Implications For Patient Carementioning
confidence: 99%